ASPECTS OF PHARMACOLOGICAL STUDY OF A NEW OXAMINE ACID DERIVATIVE - Литвинова, О.М.; Литвинов, В.С. (World of Medicine and Biology, 2014)
The influence of metoxarade on activity proteolytic enzymes of kininic system and contents of prostaglandinums is investigated. Fixed, that metoxarade inhibits process kininogenesis and, as against Acidum Acetylsalicylicum, prevents expenditure of components kallikrein-kininic system, and also reduces contents of prostaglandinums by 62,3% in comparison with experimental rats with carragenin's edema of pаd. Obtained results allow to recommend metoxarade for further study with the aim of development of a new medicine with anti-inflammatory and analgetic effects.
Keywords: oxamine acid derivatives; proteolytic enzymes of kininic system